Air pollutants and development of interstitial lung disease in patients with connective tissue disease: a population-based case–control study in Taiwan. Issue 12 (28th December 2020) - Chen, Hsin-Hua; Yong, You-Ming; Lin, Ching-Heng; Chen, Yi-Hsing; Chen, Der-Yuan; Ying, Jia-Ching; Chao, Wen-Cheng
Abstract : Objective: The aim of this study was to assess the association between air pollutant exposure and interstitial lung disease (ILD) in patients with connective tissue diseases (CTDs). Setting: A nationwide, population-based, matched case–control study in Taiwan. Participants: Using the 1997–2013 Taiwanese National Health Insurance Research Database, we identified patients with newly diagnosed CTD during 2001–2013, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), systemic sclerosis (SSc), dermatomyositis (DMtis)/polymyositis (PM) and primary Sjögren's syndrome (pSS). Primary and secondary outcome measures: Patients with newly diagnosed ILD during 2012–2013 were identified as ILD cases, and selected patients with CTD without ILD matching (1:4) the CTD cases for CTD diagnosis, age, gender, disease duration and year of ILD diagnosis date were identified as non-ILD controls. Data of hourly level of air pollutants 1 year before the index date were obtained from the Taiwan Environmental Protection Agency. The association between ILD and air pollutant exposure was evaluated using logistic regression analysis shown as adjusted ORs (aORs) with 95% CIs after adjusting for potential confounders. Results: We identified 505 newly diagnosed CTD-ILD patients, including 82 with SLE, 210 with RA, 47 with SSc, 44 with DMtis/PM and 122 with pSS. Ozone (O3 ) exposure (per 10 ppb) was associated with a decreased ILD risk in patients with CTD (aOR, 0.51; 95% CI, 0.33 to 0.79) after adjusting for potential confounders. Conclusions: A previously unrecognised inverse correlation was found between O3 exposure and ILD in patients with RA and SSc. Further studies are warranted to explore the underlying mechanisms.